Environmental, Toxicological, and Evolutionary Influences on Membrane Composition in Fish - Gonzalez, Alyssa (Université d'Ottawa / University of Ottawa, 2016)
Many factors affect membrane composition in ectotherms, including allometry, temperature, toxins such as PCB-153, and osmotic stress. This thesis seeks to describe the relationship between membrane composition, size, and phylogeny in twelve species of cypriniform fish; to describe interactions between the homeoviscous responses to temperature and to PCB-153 in goldfish and rainbow trout; and to describe the membrane response to hypoosmotic stress in goldfish. Commonalities in these patterns provide insight into shared mechanisms of phospholipid modulation. In particular, such similarities indicate whether the membrane pacemaker theory of metabolism, which connects allometric relationships between body size, membrane phospholipids, and metabolic rate, can serve as a general framework for understanding membrane composition. Chapter 2 investigates how cypriniform membrane unsaturation decreases with mass through different fatty acid substitutions than in endotherms, but these fatty acids are in turn shown to be due to the species’ relatedness to one another rather than to purely physiological causes. In Chapter 3, PCB-153 is shown to increase cholesterol in liver and brain, while high temperature primarily reduces phospholipid unsaturation. In Chapter 4, these patterns are further explored in trout. As in goldfish, cholesterol modulation is the primary response to PCB-153, whereas temperature primarily reduces phospholipid unsaturation. Trout show more pervasive fatty acid changes than goldfish in all tissues except the liver, which does not respond to PCB exposure, suggesting that PCB-153 pushes trout’s homeoviscous response to a limit that similarly-exposed goldfish do not face. Chapter 5 shows that goldfish intestines decrease membrane saturation; kidneys decrease membrane cholesterol; gills decrease neither; and muscles decrease both in response to long-term exposure to hypoosmotic conditions. The intestine and kidney are both involved in recovering ions from body fluids, but gills suppress ion loss and muscle concentrates ions from the bloodstream. Temperature, osmotic stress, PCB-153, and increasing body size are all addressed via a similar set of membrane responses in fish, which fits with the membrane pacemaker theory’s predictions regarding membrane composition, metabolic rate, and size.
Keywords: goldfish; trout; membranes; phospholipids; homeoviscous; allometry; membrane pacemaker; PCB